Sex Disparity in Characteristics, Management, and In-Hospital Outcomes of Patients with ST-Segment Elevated Myocardial Infarction: Insights from Henan STEMI Registry - Shan Wang; You Zhang; Qianqian Cheng; Datun Qi; Xianpei Wang; Zhongyu Zhu; Muwei Li; Junhui Zhang; Dayi Hu; Chuanyu Gao; On behalf of Henan STEMI registry study group (Cardiology Research and Practice)
Background. Women hospitalized with ST-elevation myocardial infarction (STEMI) experience higher risk of early mortality than men. We aimed to investigate the potential impact of risk factors, clinical characteristics, and management among gender-related risk differences. Method. We analyzed 5063 STEMI patients prospectively enrolled from 66 hospitals during 2016–2018 and compared sex differences in mortality, death, or treatment withdrawal and main adverse cardiovascular and cerebrovascular events (MACCE) using the generalized linear mixed model, following sequential adjustment for covariates. Results. Women were older and had a higher prevalence of hypertension (53.3% vs. 41.1%, P<0.001) and diabetes (24.5% vs. 15.2%, P<0.001). Eligible women were less likely to receive reperfusion therapy (56.1% vs. 62.4%, P<0.001); the onset to first medical contact (FMC) (255 vs. 190 minutes, P<0.001), onset to fibrinolysis (218 vs. 185 minutes, P<0.001), and onset to percutaneous coronary intervention (PCI) (307 vs. 243 minutes, P<0.001) were significantly delayed in women. The incidence of in-hospital death (6.8% vs. 3.0%, P<0.001), death or treatment withdrawal (14.5% vs. 5.6%, P<0.001), and MACCE (18.5% vs. 9.4%, P<0.001) were notably higher. The gender disparities persist in death (OR: 1.61, 95% CI: 1.12–2.33), death or treatment withdrawal (OR: 1.68, 95% CI: 1.26–2.24), and MACCE (OR: 1.37, 95% CI: 1.08–1.74) after adjustment for covariates. Among possible explanatory factors, age (−58.46%, −59.04%, −62.20%) and cardiovascular risk factors (−40.77%, −39.36%, −41.73%) accounted for most of the gender-associated risk differences. Conclusions. Women experienced worse in-hospital outcomes, and age and cardiovascular risk factors were major factors influencing sex-related differences. The sex disparity stressed the awareness and importance of quality improvement efforts against female patients in clinical practice.